The Plant Immunity Regulating F-Box Protein CPR1 Supports Plastid Function in Absence of Pathogens - Hedtmann, Christiane; Guo, Wei; Reifschneider, Elena; Heiber, Isabelle; Hiltscher, Heiko; van Buer, Jörn; Barsch, Aiko; Niehaus, Karsten; Rowan, Beth; Lortzing, Tobias; Steppuhn, Anke; Baier, Margarete (Frontiers in Plant Science, 2017)
The redox imbalanced 6 mutant (rimb6) of Arabidopsis thaliana was isolated in a genetic screening approach for mutants with defects in chloroplast-to-nucleus redox signalling. It has an atypically low activation status of the 2-Cys peroxiredoxin-A promoter in the seedling stage. rimb6 shows wildtype-like germination, seedling development and greening, but slower growth and reduced biomass in the rosette stage. Mapping of the casual mutation revealed that rimb6 carries a single nucleotide polymorphism in the gene encoding CONSTITUTIVE EXPRESSER OF PATHOGENESIS RELATED (PR) GENES 1, CPR1 (At4g12560), leading to a premature stop codon. CPR1 is known as a repressor of pathogen signalling and regulator of microtubule organization. Allelism of rimb6 and cpr1 revealed a function of CPR1 in chloroplast stress protection. Expression studies in pathogen signalling mutants demonstrated that CPR1-mediated activation of genes for photosynthesis and chloroplast antioxidant protection is, in contrast to activation of pathogen responses, regulated independently from PAD4-controlled salicylic acid (SA) accumulation. We conclude that the support of plastid function is a basic, SA-independent function of CPR1.